Estrategia para el proceso de enseñanza-aprendizaje en la catedra de oratoria forense y su incidencia en el desempeño del abogado en el sistema oral de justicia - Tamaz Esterilla, Mirta Andrea (2025)
The purpose of this research is to develop a teaching-learning strategy, for the improvement of orality and its incidence in the performance of the lawyer, of the students of the Law School of the Universidad Regional Autónoma de los Andes, the methodology used is the survey, the questionnaire of questions, the study population, represented by the students of the chair of Law. This research is conformed, by the introduction in which are exposed: the background, the general and specific objectives, the problem that is solved with the present work. It is composed of three chapters: In the first chapter related to the theoretical foundation where the analyses and conceptions that have been found on the subject raised, the dissimilar criteria and similarities of different authors on teaching-learning are identified, and followed by themes and sub-themes. In the second, it covers the methodological framework, the approach of the research proposal is directed to a learning strategy for the improvement of orality in the training of legal professionals. In the third chapter the guidelines of the proposal are designed and finally the conclusions, recommendations, bibliography and annexes are presented.